Flight & anchor - Kornher-Stace, Nicole (Tachyon Publications LLC, 2023)
Stellaxis operatives 06 and 22 have escaped. Years ago, they survived a corporate civil war; Stellaxis kidnapped and modified them into celebrity supersoldiers. But 06 and 22 have finally broken free from their barracks. They flee into a strange city they barely remember, trying to remain anonymous while their faces appear on billboards. It will be an expensive disaster for the director of the supersoldier program if word gets out about the escaped operatives. But she has paired them for a reason: 06 to aggressively engage, 22 to keep her in check. One flight, one anchor: a perfect team if they would just return to their rightful place with her. If not, all operatives' days are numbered.